Tác động của COVID-19 và cơ chế phục hồi của các công ty giao nhận vận tải hàng xuất nhập khẩu tại Thành phố Hồ Chí Minh - Nguyễn Thanh , Hùng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
COVID-19 is an unprecedented global crisis and its negative impact on businesses and chains has been widely discussed. Thus, the restructuring of supply chains and businesses after COVID-19 is increasingly attracting the attention of businesses and researchers. However, there are not many quantitative studies on this issue. Based on supply chain recovery theory and dynamic capacity theory, this study examines how freight forwarders in the transportation supply chain restructure their businesses to become more agile and resilient. more competitive. Through analyzing the structural equation modeling of data from 504 senior managers and examining the response strategies of freight forwarding companies by SmartPLS software, the study determines how a freight forwarder can withstand and overcome the pandemic to develop. This finding contributes to related theories, especially the theory of post-crisis supply chain recovery, practices and sustainable development goals of freight forwarders in the face of future crises.